How much do avian predators influence cyclic bank vole populations? An experiment during a peak year - Ylönen, H.; Viitala, J.; Mappes, T. (Finnish Zoological and Botanical Publishing Board, 1991)
The influence of avian predators on bank vole (Clethrionomys glareolus) populations in four 0.5-ha enclosures was studied in central Finland in 1988. Two of the enclosures were covered with nets to keep out birds of prey, and two were left open to avian predation. A fence of metal sheet and continuous trapping kept out small mustelids during the breeding season. The only avian predators observed in the area throughout the year were the Ural owl (Strix uralensis) and the tawny owl (Strix aluco) and during summer the common buzzard (Buteo buteo). During autumn and winter pygmy owls (Glaucidium passerinum) was present in the study area. No Tengmalm's owls (Aegolius funereus) were observed around the area. During late winter and spring, the highest density of voles was observed in one of the open enclosures. No evidence of the influence of avian predators could be observed. During the summer the net covers had no effect on the survival of the voles; the highest density, with 100% survival of the young, was observed in an open enclosure. We suggest that avian predators have only a slight influence on breeding bank vole populations during a peak year in a patchy environment with boreal spruce forest. An explanation could be that bank voles are only an alternative prey for avian predators when field voles (Microtus agrestis) have high densities in more open habitats at the same time. The heterogeneity of the habitat and the dominance of the Ural owl in the owl community could also play a role. peerReviewed